KOMUNIKASI POLITIK MUHAMMAD DWIKI RAMADHANI DALAM MEREBUT DUKUNGAN KALANGAN GENERASI MILENIAL PADA PEMILU 2019 - Linawati Linawati; Rialdo Rezeky M L Toruan; Purba Indra Gumelar; Khairunnisa Al-Araf (Jurnal Pustaka Komunikasi, 2022)
This study examines the political communication strategy of 22-year-old Muhammad Dwiki Ramadhani who was able to win the 2019 election so that he became the youngest member of the Tangerang City DPRD from the millennials. The importance of studying communication strategy as one of the studies of political communication strategies, in addition to enriching the study of science from political communication strategies and can also be used in this case Public Relations and political consultants to apply political communication strategies so that they can win elections with the right political communication strategies. The purpose of this study is to analyze the political communication strategy of the millennial generation so that it becomes one of the concepts offered for the use of political communication strategies. This research uses qualitative research methods with the type of case study research, where researchers in collecting data use in-depth interviews and observation and documentation studies. So that scientific studies of political communication strategies are described in depth. The results showed that Muhammad Dwiki Ramdhani's political communication strategy applied political communication management theory through the stages of segmenting, targeting, and positioning.